STUDI LITERATUR TENTANG EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF DALAM MENINGKATKAN KETERAMPILAN GERAK DASAR PADA PESERTA DIDIK - Ely Yuliawan; Alikah Lesmawati; Rama Mardinata Putra; Bayu Kurniawan; Sigit Arya Yudhistira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This literature review aims to analyze the effectiveness of cooperative learning models in improving students’ fundamental movement skills. Data were obtained from ten national journals published between 2021 and 2025 related to cooperative learning in physical education. The findings indicate that cooperative learning models such as Jigsaw, STAD, TGT, Think-Pair-Share, Numbered Heads Together, and game-based cooperative learning significantly enhance fundamental movement skills, including locomotor, non-locomotor, and manipulative abilities. Group interaction, active participation, and collaborative learning environments are key factors contributing to this improvement. The study concludes that cooperative learning is an effective instructional approach and can be broadly implemented in physical education classes at the elementary school level.